A novel tool for immersive authoring of experiential learning in virtual reality - Cassola, Fernando (2021)
Training in VR can reduce risks and costs while allowing frequent and diversified experiential learning activities. We present a novel VR immersive authoring tool for experiential learning courses with industrial machinery. A trainer can create a course from scratch, defining all its components (structure, models, tools, and settings). The actions which trainees should perform can be specified by demonstration. After completing the course, trainees’ actions will be matched against the trainer’s.